‘Saved from the sordid axe’: representation and understanding of pine trees by English visitors to Italy in the eighteenth and nineteenth century - Piana, Pietro; Watkins, Charles; Balzaretti, Ross (Taylor & Francis, 2016)
Pine trees were frequently depicted and celebrated by nineteenth century English artists and travellers in Italy. The amateur artist and connoisseur Sir George Beaumont was horrified to discover in 1821 that many Roman stone pines were being felled and paid a landowner to preserve a prominent tree on Monte Mario. William Wordsworth saw this tree in 1837 and celebrated that it had been ‘Saved from the sordid axe by Beaumont's care’. Pines continued to be painted by amateurs and professionals including Elizabeth Fanshawe, William Strangways, Edward Lear, John Ruskin. These trees were also an important element of local agriculture; in parts of Liguria they were grown in vineyards in an unusual type of coltura promiscua providing both support for the vines and fertiliser from pine needles; in Tuscany and Ravenna pine plantations and forests were an important source of pine nuts. In this paper we combine the analysis of local land management records, paintings and traveller’s accounts to reclaim differing understandings of the role of the pine in nineteenth century Italy.